2022
DOI: 10.1093/tropej/fmac043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Cerebrospinal Fluid Procalcitonin in Neonatal Meningitis

Abstract: We aimed to study the diagnostic utility of cerebrospinal fluid (CSF) procalcitonin (PCT) in neonates with meningitis. All the neonates with sepsis who qualified for lumbar puncture were prospectively evaluated. The neonates were classified into Meningitis and No meningitis group based on predefined criteria. CSF PCT was estimated in these neonates along with cytological and biochemical parameters. A total of 113 neonates were included in the study with 29 in the meningitis group and 84 in the no meningitis gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[ 22 ] It can serve as an add-on to the diagnostic marker. [ 23 ] Studies have even found them to be more useful than serum-based assays. [ 24 ] However, this pose acts as an expensive affair.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] It can serve as an add-on to the diagnostic marker. [ 23 ] Studies have even found them to be more useful than serum-based assays. [ 24 ] However, this pose acts as an expensive affair.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, normative ranges were derived from studies on nearly asymptomatic neonates, but these values cannot be used as thresholds for diagnosing bacterial meningitis in symptomatic neonates 18 . Newer CSF biomarkers have been evaluated in a limited number of studies, but these are not yet ready for introduction in clinical practice [19][20][21][22][23][24] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…18 Newer CSF biomarkers have been evaluated in a limited number of studies, but these are not yet ready for introduction in clinical practice. [19][20][21][22][23][24] Although many studies on the role of CSF cytochemistry in neonates and young infants have been published, the thresholds used varied widely across the studies. As a result, the reported sensitivities and specificities also varied.…”
mentioning
confidence: 99%
See 1 more Smart Citation